Wave Scattering by Time-Dependent Perturbations : An Introduction - Roach, G. F. (Gary Francis) (Book collections on Project MUSE., 2007)
This book offers the first comprehensive introduction to wave scattering in nonstationary materials. G.F. Roach's aim is to provide an accessible, self-contained resource for newcomers to this important field of research that has applications across a broad range of areas, including radar, sonar, diagnostics in engineering and manufacturing, geophysical prospecting, and ultrasonic medicine such as sonograms. New methods in recent years have been developed to assess the structure and properties of materials and surfaces. When light, sound, or some other wave energy is directed at the material.